The Effect of Self-Efficacy, Perception of Organizational Support and Employee Engagement on Employee Performance - Yosi Puspita Sari; Chintya Ones Charli (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This study aims to examine how much, the effect of self-efficacy, perceived organizational support and employee engagement on Kinerja Karyawan PT. PLN (Persero) Rayon Indarung . The method of collecting data is through surveys and distributing questionnaires, with a sample of 50 respondents obtained by total sampling on the employee population of PT. PLN (Persero) Rayon Indarung as many as 50 people. The method used is Structural Equation Modeling (SEM) with partial Least Square (PLS). The results of data analysis concluded, (1.) Self-efficacy has a positive and significant effect on kinerja karyawan of employees at PT. PLN (Persero) Rayon Indarung. (2.) Perception of organizational support has a positive and significant effect on kinerja karyawan of employees at PT. PLN (Persero) Rayon Indarung. (3.) Employee engagement has a positive and significant effect on kinerja karyawan of employees at PT. PLN (Persero) Rayon Indarung. (4.) Kinerja karyawan is 41.1% which illustrates the magnitude of the influence received by the construct. employee engagement from the construct of self-efficacy and perceived organizational support or is a simultaneous influence on the construct of self-efficacy, perceived organizational support and employee attachment to Organizational Citizenship. The rest is influenced by other variables outside of this study.